Environmental migration, (im)mobility, and adaptation to droughts in the Seridó Potiguar (Sustainability in Debate, 2024)
This article examines migration decisions during the 2011–2016 drought in Seridó Potiguar, Rio Grande do Norte, Brazil, considering socioeconomic and demographic characteristics as well as perceptions of the drought. The data came from a household survey with a sample representative of urban areas in the region. Using binary logistic regression models for analysis, the results reveal that women are less likely to migrate compared to men during the drought. Workers in non-agricultural sectors also show a higher probability of migration. The greater likelihood of migration among those who perceive the drought as the main environmental problem in their city and among those who faced health issues related to water scarcity at home highlights the drought as a factor strongly associated with migration. Thus, migration emerges as a strategy for diversifying family livelihoods, particularly in the context of droughts and climate change.